DEVELOPMENT OF ACCOUNTING IN THE REPUBLIC OF UZBEKISTAN - Kunduz Ergashevna Igamberdieva (Galaxy International Interdisciplinary Research Journal, 2022)
This article examines the history of the emergence of accounting and budgetary accounting in the Republic of Uzbekistan, provides an overview of its current state and characteristic features. Particular attention is paid to how well the country’s accounting and budgetary accounting correlates with global trends and practices, and a brief overview of current reforms and their main goals is given.